Study on Steel Railings Installed on Concave- and Convex-Curved Bridge Parapet. Issue 2 (June 2014) - Itoh, Yoshito; Thanh, Le
This paper reports performance results for steel bridge railings installed on concave- and convex-curved bridge parapet based on new-type posts. Preliminary experimental tests are first conducted to examine the behaviours of these posts when subjected to a collision from a heavy steel ball. The values thus verified are then fed into the LS-DYNA 3D analysis tool to generate improved simulations for the performances of new-type curved steel railings subjected to truck collisions. For some concave road curvatures, it is found that the impact angles between the vehicle and the railings are larger than assumed in the current Japanese specifications. Some researchers and engineers suspect that a curved railing is less effective than a straight one in the same collision conditions. The purposes of this study, in addition to contributing to the further improvement of curved steel railings, are accordingly to test the validity of the said suspicion, and to investigate the performances of these new-type concave-curved steel railings under larger collision impact angles. The performance results for concave- and convex-curved railings are compared against each other as well as with the results for straight railings.